Early TLR4 Blockade Attenuates Sterile Inflammation-mediated Stress in Islets During Isolation and Promotes Successful Transplant Outcomes. Issue 9 (September 2018) - Chang, Charles A.; Murphy, Kayla; Kane, Robert R.; Lawrence, Michael C.; Naziruddin, Bashoo
Abstract : Background: During the isolation process, pancreatic islets are exposed to an environment of sterile inflammation resulting in an upregulated inflammatory state before transplantation. Toll-like receptor 4 (TLR4) has been identified as a major mediator of sterile inflammation. Therefore, we sought to determine whether early TLR4 blockade would be effective in reducing the inflammatory burden in islets pretransplant. Methods: Islets from C57BL/6 mice were treated with a TLR4 antagonist during the pancreatic ductal perfusion and digestion steps of the isolation process. Islets were then analyzed for inflammation by RT-PCR and Western blot, and for viability and function in vitro. A syngeneic transplant model using a marginal mass of islets transplanted intraportally into mice with streptozotocin-induced diabetes was used to study transplant outcomes after early TLR4 blockade. Results: Diabetic mice receiving 150 islets treated with early TLR4 blockade achieved euglycemia at a higher rate than mice receiving untreated islets (75% vs 29%; P < 0.05) and had improved long-term function ( P < 0.05). Serum markers for islet damage and inflammation were significantly reduced posttransplant ( P < 0.05). Both the expression of key inflammatory genes and the activation of mitogen-activated protein kinases were reduced by early TLR4 blockade. Islet viability was improved ( P < 0.05) while preserving islet insulin secretory capacity postisolation. Conclusions: Early TLR4 blockade protects islets from sterile inflammation-mediated stress sustained during isolation and promotes positive transplant outcomes. Our findings support the use of early TLR4 blockade during clinical islet isolation procedures to reduce pretransplant inflammation and improve transplant outcomes. Abstract : TLR4 blockade with TAK-242, a small molecular inhibitor, protects islets from sterile inflammation-mediated stress in a syngeneic transplant model using a marginal mass of islets transplanted intraportally into mice with streptozotocin-induced diabetes. Supplemental digital content is available in the text.